PENGARUH PROFESIONALISME, PENGALAMAN, DAN MOTIVASI TERHADAP KUALITAS AUDIT (Studi Empiris Pada Kantor Akuntan Publik Di Kota Pekanbaru, Padang, Dan Batam) - Dahlan Azmi; Andreas Andreas; Silalahi Paulus Sem (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2022)
This studied aims to analyze the influence of profesionalism, experience and motivation on audit quality. The objects of this research are all the auditor has worked at Kantor Akuntan Publik at Pekanbaru, Padang and Batam City. The data were analyzed by linear regression method and SPSS program version versi 17. The variable under study is audit quality as dependent variables and profesionalism, experience and motivation as independent variables. The results of the study show that profesionalism has an influence affect on audit quality with a significance value of 0,010, experience has an influence affect on audit quality with significance value of 0,004 and motivation has an influence affect on audit quality with significance value of 0.000, The results of this study also show that the coefficient of Adjusted R Square is 79,4%. Each independent variable, giving a strong influence on the dependent variable, meaning that the independent variable can explain dependent variable well. While the rest is influenced by other variables not included in the regression model is not included in this study.Keywords: Audit Quality, Profesionalism, Experience, Motivation